2021
DOI: 10.3329/bjns.v10i2.53777
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Intraventricular Non-Hodgkin Lymphoma – A Rare Case Report

Abstract: Lymphoma of the central nervous system can present with a wide variety of clinical symptoms and imaging characteristics which can be challenging for radiologist as well as neurosurgeons to deal with. Primary CNS lymphoma (PCNSL) accounts for 1% of all primary brain tumors which is a rare variant of extranodal non-Hodgkin’s lymphoma. We report a case primary central nervous system Non-Hodgkins lymphoma presenting a multiple intraventricular and periventricular masses in a 14 years young man with severe headache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…Besides the above-mentioned articles, we found two case studies (in 2019 and 2021) on childhood NHL in Bangladesh. Hossain et al (2021) reported a case study on a 14-year-old boy with primary CNS lymphoma (PCNSL), a type of NHL that arises in the central nervous system [ 34 ]. According to the study, this is the first instance of primary central nervous system non-Hodgkin lymphoma (PCNSL) that affected the lateral, third, and periventricular regions.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the above-mentioned articles, we found two case studies (in 2019 and 2021) on childhood NHL in Bangladesh. Hossain et al (2021) reported a case study on a 14-year-old boy with primary CNS lymphoma (PCNSL), a type of NHL that arises in the central nervous system [ 34 ]. According to the study, this is the first instance of primary central nervous system non-Hodgkin lymphoma (PCNSL) that affected the lateral, third, and periventricular regions.…”
Section: Reviewmentioning
confidence: 99%
“…PCNSL is treated with systemic or intrathecal chemotherapy and radiotherapy, not surgery. A restricted biopsy can diagnose problems, reducing side effects [34]. In the case study reported by Hafiz et al (2019), a two-year-old male child was brought to the Department of Pediatric Hematology and Oncology at BSMMU.…”
Section: Epidemiology Of Nhl In Pediatric Patients In Bangladeshmentioning
confidence: 99%